In dienst van de stad. Vrouwen in stedelijke ambten, Holland 1500-1800 - van der Heijden, Manon; Schmidt, Ariadne (TSEG - The Low Countries Journal of Social and Economic History, 2007)
Women’s work in public services in early modern towns in Holland, 1500-1800This article analyses the influence of professionalization and the broader pro-cess of bureaucratization on female labour participation in the public service sector in early modern towns in Holland. Contrary to what is suggested in lit-erature, women could be found in a broad range of public offices and develop-ments in the sector did not lead to the exclusion of women in the course of the early modern period. Women occupied mainly jobs in the lowest ranges of the sector and performed work which was barely affected by professionalization. The strong gender division of labour furthermore prevented the exclusion of women. Instead, specialization and diversification of tasks resulted in a broad-ening of work opportunities, not only for men, but for women as well.